Cardiovascular variability before and after delivery: recovery from arterial stiffness in women with preeclampsia 4 days post partum. (February 2014) - Walther, Thomas; Voss, Andreas; Baumert, Mathias; Truebner, Sandra; Till, Holger; Stepan, Holger; Wessel, Niels; Faber, Renaldo
<x xml:space="preserve">Abstract</x> Objective: We studied the short-term response of autonomic control to delivery in normal pregnancies and pregnancies with preeclampsia (PE). Methods: Fourteen healthy pregnant women and 13 women with PE were monitored within four days before and four days after delivery and compared to values of 14 non-pregnant women as controls using high-resolution electrocardiogram and noninvasive continuous blood pressure monitoring. Results: In PE, blood pressure remained elevated four days postpartum, but markers for arterial stiffness normalized. In contrast, none of heart rate variability and baroreflex sensitivity parameters, altered due to either pregnancy or disease, were normalized 96 h after delivery. Conclusion: Four days after delivery, the maternal cardiovascular system is still strongly affected by pregnancy independent of the health status.